Brief Mindfulness Meditation Induces Gray Matter Changes in a Brain Hub - Rongxiang Tang; Karl J. Friston; Yi-Yuan Tang (Neural Plasticity)
Previous studies suggest that the practice of long-term (months to years) mindfulness meditation induces structural plasticity in gray matter. However, it remains unknown whether short-term (<30 days) mindfulness meditation in novices could induce similar structural changes. Our previous randomized controlled trials (RCTs) identified white matter changes surrounding the anterior cingulate cortex (ACC) and the posterior cingulate cortex (PCC) within 2 to 4 weeks, following 5-10 h of mindfulness training. Furthermore, these changes were correlated with emotional states in healthy adults. The PCC is a key hub in the functional anatomy implicated in meditation and other perspectival processes. In this longitudinal study using a randomized design, we therefore examined the effect of a 10 h of mindfulness training, the Integrative Body-Mind Training (IBMT) on gray matter volume of the PCC compared to an active control—relaxation training (RT). We found that brief IBMT increased ventral PCC volume and that baseline temperamental trait—an index of individual differences was associated with a reduction in training-induced gray matter increases. Our findings indicate that brief mindfulness meditation induces gray matter plasticity, suggesting that structural changes in ventral PCC—a key hub associated with self-awareness, emotion, cognition, and aging—may have important implications for protecting against mood-related disorders and aging-related cognitive declines.